SAN VICENTE DE MORAVIA A LA LUZ DEL CENSO DE 1927 - Enríquez Solano, Francisco; Enríquez Solano, Francisco (Universidad de Costa Rica, 2005)
In this article it is analized how is made the territorial conformation process from a institutional perspective, based on the historical construction of the local identity to get the county status. A population dinamic analysis is developed from the 1927 census database, also it is studied the process that transforms this community into a coffee community and, finally, it is explained how this county represents a particular case of property concentration in the central valley of Costa Rica.